DIGITAL TRANSFORMATION IN EDUCATION: ANALYZING THE EFFECTIVENESS OF PAPERLESS CLASSROOMS IN MALAYSIAN UNIVERSITIES - Mat Nawi , Nur Ainatul Mardiah; Zulkifli , Siti Zulaikha; Abdullah , Nurulannisa; Mohd Shukry , Amira Idayu; Abdul Hamid , Haslinda; Mohd Affandi , Najatul Afiqah; Abu Bakar , Normashidayu (Journal of Islamic, Social, Economics and Development, 2024)
This study aims to establish how the concepts of paperless classroom enhance learning and to further explore the students' perception of paperless classroom. This study focus on the Malaysian universities particularly on the effects of transformation to paperless environment on the students’ engagement, motivation, performance and learning experience. The questionnaires were administered online and to the students of both public and private universities. The findings indicate that paperless classroom is beneficial since it provides opportunities as well as flexibility for learning and improving motivational level. Furthermore, this research explores that the students expressed mixed opinions, where some of the respondents acknowledge the advantages of digital learning, which includes improved motivation and easier access to resources. In addition, respondents expressed their concerns regarding technological readiness, digital literacy, and the financial costs of participating in a paperless classroom. The findings provide valuable insights for policymakers and educational institutions seeking to enhance digital transformation in education. Future research should further explore the long-term effects of paperless classrooms on various academic disciplines and the role of educators in facilitating this digital transformation. Furthermore, further research should focus on the population and data sampling process.